Recuperar la memoria histórica de la Universidad Politécnica Salesiana en los Centros de Apoyo de Quito y Wasakentsa de la Carrera de Educación Intercultural Bilingüe por los 22 años de la Universidad Politécnica Salesiana - Andrade Zúñiga, Dennisse Alejandra (2017)
The present titling product is the result of the field research conducted at the Wasakentsa Support Center of the Bilingual Intercultural Education Career (EIB) at Quito Headquarters. This project has a product made through a communicative project of reporter, investigative, editorial, designed and designed in the genre of journalistic chronicle. It is important to publicize the impact of Salesian education in the aforementioned places, seeing the need to revitalize the historical and social memory of the Wasakentsa community and strengthen the Bilingual Intercultural Education Career (EIB) at Quito Headquarters with up-to-date information of its students, teachers and graduates for the record of history. The research carried out in the support centers makes it possible to raise awareness about cultural, religious and human issues, as an input for the Salesian community at the national level, contributing in a way to the Salesian mission in Ecuador. The importance of education for indigenous communities is a contribution to social, economic and political progress.